Comparative study of multiple black hole attacks solution methods in manet using AODV routing protocol - Kordi, Elahe Fazeldeh (2014)
Mobile Wireless Ad Hoc Networks (MANET) are non-centralized wireless networks that can be formulated without the need for any pre-existing infrastructure in which each node can act as a router. It must discover its local neighbours and through them it will communicate to nodes that are out of its transmission range. Various features like open medium, dynamic topology, lack of clear lines of defence, makes MANET vulnerable to security attacks. Ad hoc On-demand Distance Vector routing (AODV) is one of the best and popular routing algorithms. AODV is severely affected by well-known black hole attack in which a malicious node injects a faked route reply message that it has a fresh route to destination. In this thesis, MANET performance against single black hole attack has compared with its performance against multiple black hole attacks by using Intrusion Detection System (IDSAODV) routing protocol (Dokurer, 2006). The result are analysed using NS-2.35, through various network parameter bases: total drop packets, end to end delay, packet delivery ratio and routing request overhead. The results indicate IDSAODV solution method which is presented for single black hole attack before, can be used effectively for decreasing total drop packets and improving packet delivery ratio against multiple black hole attacks, also. But, the method doesn’t have significant effect for improving end to end delay and routing request overhead.